2010
DOI: 10.1111/j.1752-4598.2010.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of prescribed fire on saproxylic beetles in loblolly pine logs

Abstract: 1. Studies addressing the immediate impacts of fire on forest arthropod communities and their implications for conservation are few, particularly for species within dead wood. To investigate the effects of fire on saproxylic beetles (Coleoptera), we randomly assigned large-diameter loblolly pine (Pinus taeda L.) logs to a forest scheduled for a prescribed burn (i.e. a low-intensity surface fire) or to an adjacent unburned forest in Georgia, USA.2. Beginning 5 days after the fire, the logs were placed in rearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…lightly burned woody debris or dead wood located in small unburned patches enclosed within the burn) cannot be excluded at this point since epigeic arthropods may survive to low severity burns (Ahlgren, 1974;Paquin and Coderre, 1997;Wikars and Schimmel, 2001). Ulyshen et al (2010) recently reported that saproxylic beetles may survived to prescribed, low intensity fires. However, the volume of local pre-fire CWD and low fire severity at the nearby scale did not have such positive effect on the local abundance of saproxylic species.…”
Section: Potential Effect Of Dispersal From Other Habitatsmentioning
confidence: 98%
See 1 more Smart Citation
“…lightly burned woody debris or dead wood located in small unburned patches enclosed within the burn) cannot be excluded at this point since epigeic arthropods may survive to low severity burns (Ahlgren, 1974;Paquin and Coderre, 1997;Wikars and Schimmel, 2001). Ulyshen et al (2010) recently reported that saproxylic beetles may survived to prescribed, low intensity fires. However, the volume of local pre-fire CWD and low fire severity at the nearby scale did not have such positive effect on the local abundance of saproxylic species.…”
Section: Potential Effect Of Dispersal From Other Habitatsmentioning
confidence: 98%
“…Early coloniz- Duelli, 2004). Potential source habitats may include woody debris located in unburned forests in the surroundings, other recently burned stands (Saint-Germain et al, 2008) or in the burned habitat itself, as one cannot exclude that fire does not kill all organisms (Ulyshen et al, 2010). Large distance from source habitats or reduced local populations before fire may negatively affect the probability of a species to be collected in a suitable habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Although their heat tolerances (~44 °C) [38], fall far below the temperatures reached on the forest floor during typical burns [39], these organisms could have easily found refuge several centimeters beneath the soil surface [40]. They may also have been able to survive fires within dead wood as has been shown for other insects [41]. Furthermore, the availability of dead wood was not affected by fire frequency and charring does not deter feeding by these organisms [42] so their food resources were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, past research has demonstrated benefits of these treatments, applied singularly or together, to game and non-game animals such as white-tailed deer (Odocoileus virginianus Zimmerman, 1780; e.g., Mixon et al, 2009;Iglay et al, 2010b), eastern wild turkey (Meleagris gallopavo silvestris Linnaeus, 1758; e.g., Dickson and Wigley, 2001;Miller and Conner, 2007), northern bobwhite (Colinus virginianus Linnaeus, 1758; e.g., Guynn et al, 2004;Miller and Miller, 2004;Welch et al, 2004), and songbirds (e.g., Sladek et al, 2008;Iglay, 2010). Past research regarding invertebrate responses to prescribed fire and imazapyr is primarily focused on fire (e.g., Gandhi et al, 2001;Hanula et al, 2009;Ulyshen et al, 2010). However, research regarding carabid (Coleoptera: Carabidae) responses to these treatments is lacking (Cobb et al, 2007;Iglay, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Research regarding carabid responses to fire has been primarily conducted in Minnesota, Pacific Northwest, and Canadian forests (e.g., McCullough et al, 1998;Gandhi et al, 2001;Niwa and Peck, 2002) with some recent studies in the southeastern United States (e.g., Hanula and Wade, 2003;Hanula et al, 2009;Ulyshen et al, 2010). Few studies have investigated effects of forest herbicide application on arthropods with most limited to site preparation applications (Salminen et al, 1996;Bell et al, 1997;Duchesne et al, 1999) and to our knowledge, information regarding carabid responses to fire with or without imazapyr is limited to our research effort and post-fire salvage logging in boreal forest (Cobb et al, 2007).…”
Section: Introductionmentioning
confidence: 99%